Characterization of Zika Virus Endocytic Pathways in Human Glioblastoma Cells - Li, Mei; Zhang, Di; Li, Chuntian; Zheng, Zifeng; Fu, Ming; Ni, Fengfeng; Liu, Yalan; Du, Tao; Wang, Hanzhong; Griffin, George E.; Zhang, Mudan; Hu, Qinxue (Frontiers in Microbiology, 2020)
Zika virus (ZIKV) infections can cause microcephaly and neurological disorders. However, the early infection events of ZIKV in neural cells remain to be characterized. Here by using a combination of pharmacological and molecular approaches and the human glioblastoma cells T98G as a model, we first observed that ZIKV infection was inhibited by chloroquine and NH4Cl, indicating a requirement of low intracellular pH. We further showed that dynamin is required as ZIKV entry was affected by the specific inhibitor dynasore, siRNA knockdown of dynamin or by expressing the dominant negative K44A mutant. Moreover, ZIKV entry was significantly inhibited by chlorpromazine, pitstop2, or siRNA knockdown of clathrin heavy chain, indicating an involvement of clathrin-mediated endocytosis. In addition, genistein treatment, siRNA knockdown of caveolin-1 or overexpression of a dominant negative caveolin mutant impacted ZIKV entry, with ZIKV particles being observed to colocalize with caveolin-1, implying that caveola endocytosis can also be involved. Furthermore, we found that endocytosis of ZIKV is dependent on membrane cholesterol, microtubules and actin cytoskeleton. Importantly, ZIKV infection was inhibited by silencing of Rab5 and Rab7, while confocal microscopy showed that ZIKV particles localized in Rab5- and Rab7-postive endosomes. These results indicated that, after internalization, ZIKV likely moves to Rab5-positive early endosome and Rab7-positive late endosomes before delivering its RNA into the cytoplasm. Taken together, our study for the first time described the early infection events of ZIKV in human glioblastoma cells T98G.